Determination of vp/vs on Bali Province: Case of Bali Earthquake March 22, 2017 - Auliyah, Febi Niswatul; Suarbawa, Komang Ngurah; Indira, Indira (BULETIN FISIKA; Vol 19 No 2 (2018): BULETIN FISIKA, 2018)
P-wave velocity and S-wave velocity have been investigated in the Bali Province by using earthquake case studies on March 22, 2017. The study was focused on finding out whether there were anomalies in the values of v p /v s before and after the earthquake. Earthquake data was obtained from the Meteorology, Climatology and Geophysics Agency (BMKG) Region III Denpasar, which consisted of the main earthquake on March 22, 2017 and earthquake data in August 2016 to May 2017. Data was processed using the wadati diagram method, obtained that the v p /v s on SRBI, IGBI, DNP and RTBI stations are shifted from 1.5062 to 1.8261. Before the earthquake occurred the anomaly of the value of v p /v s was found on the four stations, at the SRBI station at 10.35%, at the IGBI station at 16.16%, at DNP station at 12.27% and at RTBI station at 4.62%.